Teknik Pembibitan Spesies Kayu Kuku (Pericopsis mooniana) untuk Reklamasi Lahan Bekas Tambang (Nursery Technique of Pericopsis mooniana for Post-Mining Land Reclamation) - Suhartati Suhartati; Didin Alfaizin (Balai Penelitian Dan Pengembangan Teknologi Hasil Hutan Bukan Kayu, 2018)
As one of the problems in the post-mining land reclamation are selection and utilization of local/native species for guarantee of success reclamation, because these types of relatively more adaptive. Pericopsis mooniana Thw. is one of the local species Sulawesi which capable of adapting to unproductive land, but the data and information via the research has not been done. This study aims to determine the potensial of Pericopsis to be used on land-reclamation on post-mining land. The study was conducted in a greenhouse BPPLHKM, in Makassar with four months between May and August 2016 and using a completely randomized design (CRD) with 6 treatments media composition. The results showed that the potential of Pericopsis more efficient use of post-mining land, or mix media of soil, compost and sand, compared to adding mycorrhiza isolates and NPK fertilizer for reclamation. The mean value Seed Quality Index of ≥ 0,50 obtained with a mean increase in height and diameter of seedlings of ≥ 19 cm and ≥ 2 mm, and the mean of top root ratio is 2 point. Pericopsis nursery does not require additional fertilizer, although nutrient-poor conditions as well as post-mining land for the earlier step in planting.